PENGARUH JENIS MEDIA KULTUR TERHADAP KONSENTRASI BIOMASSA Nannochloropsis sp. - Nabila Marthia (Department of Food Technology, Universitas Pasundan, Bandung, 2020)
This study aims was to determine the effect of media type on biomass concentration and chlorophyll content in Nannochloropsis sp. and determine the best type of media for the highest chlorophyll production in this microalgae. The variables observed were the optimum growth and harvest time for Nannochloropsis sp., biomass concentration, and chlorophyll content from biomass extraction. The results showed that the wet biomass concentration value of Nannochloropsis sp. is 10.98 g / L for Walne media, and 5.10 g / L for Guillard media. Chlorophyll content extracted from dry biomass in microalgae Nannochloropsis sp. with Walne culture media was higher than Guillard media with a total chlorophyll of 353.045 µg / mL. So that the best chlorophyll production is cultivation using Walne culture media.